Legal Status of the Church before the States - Santos Díez, José Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
A proof of the attention paid by the States to the religious phenomenon is the recognition of the Churches in the state code. Thought is given to the legal identity of the Churches and to the conditions needed for their recognition by the State. Special attention is paid to the Holy See as a legal entity in international law.